PARTISIPASI MASYARAKAT DALAM PERENCANAAN DAN PEMELIHARAAN PEMBANGUNAN DRAINASE JALAN KOMODOR YOS SUDARSO - Muhammad Rum E.21109074 (FISIP Universitas Tanjungpura, 2013)
The Article want to describs the form of participation from the society in maintenance the result of development and analyse the forms of participation in the plan development. The Method that be used is qualitative with the descriptive approach. Result of this research indicate that the drainage development as long as 4 km represent the society proposal. Society proposal for drainage development of early from process of Musrenbang of Chief at Village of Sungai Jawi. A lot of society proposal in forum Musrenbang finally cannot be realized, because assumed insufficient of its benefit strength for the sake of a lot of party. This matter differ from the drainage development, where besides as expectation/society proposal also enter in Governmental program from pontianak city, so that earn the realization properly. Therefore, recommended from this study is pursuant to initiative aspiration, and also to develope democracy from grassroot. Others, so that development hence for people it is anykind evaluate, and involpe the people to maintenance the result of development. Keywords: Kinds of participate, plan of village development and maintenance of build result.